Review Of Value Added Tax On Palm Kernel Expeller After The Supreme Court Decision (Putusan Mahkamah Agung) Number 70P/HUM/2013 - Aprian, Galu Bernie; Irawan, Ferry (Politeknik Keuangan Negara STAN, 2023)
Palm Kernel Expeller (PKE) is a by-product of the secondary processing of fresh fruit bunches (FFB). The problem related to VAT arises when there are differences in interpretation of the regulations relating to the transaction of PKE, whether transcation of PKE is subject to VAT which is subject to tax invoice code or transcation which receives facilities of the exemption from VAT which are subject to tax invoice code 08. This research uses a normative-empirical approach by using main documents in the form of supreme court decision on judicial review of PKE case. The research results show that the judge concludes that the implementing regulations for the transaction of PKE used for animal feed must be in line with Supreme Court Decisions Number 70P/HUM/2013 and SE-24/PJ/2014. Second, both tax authorities and taxpayers must find out information about PKE’s buyers because PKE has other benefits besides being used for animal feed. If it is used for other things, then the transaction is contrary to the aim and purpose of providing VAT facilities in the form of exemption.